Análisis macrosísmico del terremoto de buena vista de Pérez Zeledón, 3 de julio de 1983 (ms = 6,1), Costa Rica - Mora, Mauricio M.; Peraldo, Giovanni (Revista geológica de América central, 2010)
This research integrates information from documents and testimonies about the effects of the Buenavista Earthquake, July 3rd 1983 (Ms = 6,1) in Costa Rica. From this documentation, it has been possible to reconstruct a local intensity map, and furthermore to understand the perception and social representations that the population draw as explanations about the earthquake source. Maximum intensities occurred northward of Rivas town (VIII-IX), showing an elongated pattern striking NNW. The integration of all primary and secondary information which has been taken and analyzed, suggests a seismic source striking E-W or NW-SE, located north of Buenavista town. The social interpretations to explain the Buenavista Earthquake were focused on ?divine punishment? (?the final judgement?), volcanic activity or collapsing caverns.